Variation of HbA1c with Hemoglobin level: A comparative study between High Performance Liquid Chromatography and Immunochromatography Analyzer - Bhattarai, Arabinda Mohan; Parajuli, Sulochana; Pradhananga, Salina (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: The measurement of glycated hemoglobin (HbA1c) is an established procedure in evaluating long-term glycemic control in diabetic patients. There are many factors like temperature, pH, lifespan of protein, substrate concentrations and hemoglobin levels that influence HbA1c estimation by any methods. The aim of the study is to estimate HbA1c by High Performance Liquid Chromatography (HPLC) and immunochromatography analyzer and find the influence of hemoglobin in HbA1c by both the methods. Methods: This was a descriptive, cross-sectional study carried out in the department of Biochemistry of Shree Birendra Hospital, Chhauni, Kathmandu over a period of two months from May 2021 to June 2021. We selected patients with type 2 diabetes mellitus. HbA1c was measured in EDTA blood samples by Bio-Rad D10 (HPLC method) and Nycocard (Immunochromatography method) whereas hemoglobin was estimated using Horiba Penta XLR fully automated hematology analyzer. Results: In our study of 100 known cases with type 2 diabetes mellitus, the mean hemoglobin level was 14 ± 2.09 g/dL. The mean HbA1c value obtained by Nycocard and HPLC analyzer were 7 ± 1.95 % and 7.39 ± 2.21% respectively. We found that there was a strong correlation of HbA1c values with hemoglobin levels in HPLC method p = 0.001, r = 0.6. However, we found no such correlation by Nycocard method p = 0.6, r = 0.08. Conclusion: There was a positive correlation of hemoglobin with HbA1c values obtained by HPLC method however no such variation was seen with immunochromatography method. This suggests that estimating HbA1c by HPLC methods may show decreased HbA1c with decreased hemoglobin levels and increased HbA1c with increased hemoglobin levels.